Sexual dimorphism of sharks from the amazonian equatorial coast - Silva Nunes, Jorge Luiz; Universidade Federal do Maranhão, Departamento de Oceanografia e Limnologia, Avenida dos Portugueses 1966, Cidade Universitária do Bacanga, São Luís, Maranhão, Brazil. (2015)
Sexual dimorphism is a widespread feature in several groups of vertebrates. Chondrichthyans differ sexually due to the presence of the clasper, a structure for internal fertilization, and other sexual differences in secondary characteristics. Nevertheless, studies assessing these variations are fairly rare. The main goal of this study is to identify differences in sexual dimorphism in three species of sharks from the Carcharhinidae family (Rhizoprionodon porosus, Carcharhinus porosus and Isogomphodon oxyrhynchus) using morphometric tools. A total of 213 specimens were captured in the Amazonian Equatorial Coast and analyzed using 65 morphometric characters. Discriminant analysis and The Student's t-test were used to demonstrate the morphological differences among sexes. Sexual dimorphism was reported at different levels for the three species. This study suggests that the most likely explanation for the presence of these variations is related to their reproductive characteristics and mating behavior.